1998
DOI: 10.1007/s004200050316
|View full text |Cite
|
Sign up to set email alerts
|

Exposure-response relationship in the hand-arm vibration syndrome: an overview of current epidemiology research

Abstract: The complex of vascular, neurologic, and osteoarticular disorders occurring in the upper limbs of vibration-exposed workers is called hand-arm vibration syndrome. There is epidemiologic evidence for an increased occurrence of peripheral sensorineural disorders in occupational groups working with vibrating tools. An excess risk for wrist osteoarthrosis and for elbow arthrosis and osteophytosis has been reported in workers exposed to shocks and low-frequency vibration of high magnitude from percussive tools. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
154
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(160 citation statements)
references
References 38 publications
5
154
1
Order By: Relevance
“…Bovenzi requests prospective cohort studies to establish this relationship. (3). We believe that the present study may be an important contribution to our knowledge in this area.…”
Section: Edlund Et Almentioning
confidence: 58%
See 3 more Smart Citations
“…Bovenzi requests prospective cohort studies to establish this relationship. (3). We believe that the present study may be an important contribution to our knowledge in this area.…”
Section: Edlund Et Almentioning
confidence: 58%
“…Cases of HAVS have been reported mainly in countries with colder climates but also in tropical regions (2). The most evident sensorineural symptoms are tingling and numbness of the hand, and it has been tentatively suggested that the earliest symptoms are more likely to be neurological, preceding vascular symptoms (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic variables can include population type (age, sex, size, and health), experience, body posture, and types of activities [16]. Conversely extrinsic variables can include vibration magnitude, vibration frequency, vibration axis, vibration input position, vibration duration, and other influences such as noise, heat, acceleration, and light [16,18,19]. When evaluating the biodynamic response of the human body to vibration, an understanding of the resonant frequency and transmissibility is required.…”
Section: Introductionmentioning
confidence: 99%